2004
DOI: 10.1213/01.ane.0000134803.28029.7e
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Isoflurane During Simulated Ischemia/Reoxygenation on Intracellular Calcium, Contractile Function, and Arrhythmia in Ventricular Myocytes

Abstract: Some of isoflurane's cellular actions, such as interference with intracellular Ca(2+) handling, inhibition of the respiratory chain, and the capability to produce oxygen radicals, could result in impaired cellular function during ischemia/reoxygenation (I/R). We investigated the effects of isoflurane applied during I/R on intracellular Ca(2+), oxygen radical formation, arrhythmic events, and contractile function in rat cardiomyocytes. Single ventricular myocytes were subjected to 30 min of simulated ischemia f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
8
1
Order By: Relevance
“…There is, however, data that shows it has adverse effects on myocardium. Isoflurane in certain settings can induce a rise in intracellular calcium, especially during hypoxia [11], although this rise in intracellular calcium has not been shown to have lusitopic effects [12]. In combination with levosimendan, this effect may account for the fact the experimental animals expired relatively shortly after the administration of the second dose of levosimendan.…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, data that shows it has adverse effects on myocardium. Isoflurane in certain settings can induce a rise in intracellular calcium, especially during hypoxia [11], although this rise in intracellular calcium has not been shown to have lusitopic effects [12]. In combination with levosimendan, this effect may account for the fact the experimental animals expired relatively shortly after the administration of the second dose of levosimendan.…”
Section: Discussionmentioning
confidence: 99%
“…(Quaife et al, 1991) Augmented release of oxygen radicals has been observed in the setting we employed in the presence of isoflurane during reoxygenation after simulated ischemia. (Dworschak et al, 2004a) Indirect evidence also suggests that isoflurane during metabolic inhibition enhances myoplasmic Ca 2+ accumulation via liberation of a different kind of oxygen radical species. (Dworschak et al, 2004b) The multifactorial cause of cellular dysfunction and necrosis is supported by the finding that elevated [Ca 2+ ] i results in excessive Ca 2+ dependent myofilament crossbridge cycling, which again could be prevented by butanedione monoxime that inhibits force development.…”
Section: Discussionmentioning
confidence: 99%
“…However, an enhanced liberation of oxygen radical species may also contribute to these observations. (Dworschak et al, 2004a) …”
Section: Discussionmentioning
confidence: 99%
“…The detailed I/R protocol has already been described elsewhere (8). In brief, hypoxic conditions (PO 2 Ͻ 15 mmHg) were achieved by vigorously bubbling the solution with nitrogen and introducing nitrogen under the hood of the perfusion chamber as has been demonstrated by Henderson and Brutsaert (17).…”
Section: Methodsmentioning
confidence: 99%